A Management Trinity: Employee Satisfaction, Customer Satisfaction and Economic Performance - Martins da Fonseca, Luis Miguel Ciravegna; Lopes Ferro, Ricardo (International Journal of Industrial Engineering and Management, 2016)
AManagement and Total Quality Management Theories support the importance of employee satisfaction and customer satisfaction for companies economic results and ensuring success. However, there are still some gaps concerning evidence of relationships between these three constructs. This research aims to access if there are indeed positive relationships between employee satisfaction, customer satisfaction and companies economic performance. By using a large database from a Portuguese Official Agency, framed according to the EFQM Business Excellence Model, with inputs of small and medium companies in stable industries over 10 years, 3 hypotheses were statistically tested. The results support the propositions of valid relationships between EFQM Model results criteria with evidence of positive relationships between employees satisfaction and customer satisfaction and economic performance, and between customers satisfaction and companies economic performance, which is relevant both from a theoretical and practical point of view. Article history: Received (12.08.2015); Revised (26.01.2016); Accepted (16.02.2016)